Computer programs for writing music - Whiteman, Lauren A.; Doughty, Charles; Folks, Steve; South Carolina Educational Television Network (Columbia, S.C. : S.C. ETV, 1992)
Lauren Whiteman demonstrates and discusses some solutions to the sometimes tedious task of notating compositions.
VHS format.
Clint Bryson, Keisha Johnson, Tracy Webb, cameras ; Elaine Cooper, editor.
Lauren Whiteman, instructor ; Ray Doughty, series host.
Recorded January 13, 1992.
Keywords: Musical notation; Computer composition